Assessing the co-location potential of seaweed aquaculture and offshore wind farms in UK waters using habitat suitability models - Ethan Clark; Pippa J. Moore; Rodney M. Forster; Harry Burton; Clare Fitzsimmons (Aquaculture, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Quantification of turbid wakes in offshore wind farms using satellite remote sensing - Enora M. Lecordier; Pierre Gernez; Krysia Mazik; Katharine York; Rodney M. Forster (Science of The Total Environment, 2025)

Microscale Variability in Biomass and Photosynthetic Activity of Microphytobenthos During a Spring-Neap Tidal Cycle - Jacco C. Kromkamp; Ed Morris; Rodney M. Forster (Frontiers in Marine Science, 2020)

A decline in primary production in the North Sea over 25 years, associated with reductions in zooplankton abundance and fish stock recruitment - Elisa Capuzzo; Christopher P. Lynam; Jon Barry; David Stephens; Rodney M. Forster; Naomi Greenwood; Abigail McQuatters‐Gollop; Tiago Silva; Sonja M. van Leeuwen; Georg H. Engelhard (Global Change Biology, 2018)
Phytoplankton primary production is at the base of the marine food web; changes in primary production have direct or indirect effects on higher trophic levels, from zooplankton organisms to marine mammals and seabirds. Here, we present a new time‐series on gross primary production in the North Sea, from 1988 to 2013, estimated using in situ measurements of chlorophyll and underwater light. This shows that recent decades have seen a significant decline in primary production in the North Sea. Moreover, primary production differs in magnitude between six hydrodynamic regions within the North Sea. Sea surface warming and reduced riverine nutrient inputs are found to be likely contributors to the declining levels of primary production. In turn, significant correlations are found between observed changes in primary production and the dynamics of higher trophic levels including (small) copepods and a standardized index of fish recruitment, averaged over seven stocks of high commercial significance in the North Sea. Given positive (bottom‐up) associations between primary production, zooplankton abundance and fish stock recruitment, this study provides strong evidence that if the decline in primary production continues, knock‐on effects upon the productivity of fisheries are to be expected unless these fisheries are managed effectively and cautiously.

Implementing and Innovating Marine Monitoring Approaches for Assessing Marine Environmental Status - Roberto Danovaro; Laura Carugati; Marco Berzano; Abigail E. Cahill; Susana Carvalho; Anne Chenuil; Cinzia Corinaldesi; Sonia Cristina; Romain David; Antonio Dell'Anno; Nina Dzhembekova; Esther Garcés; et al. (Frontiers in Marine Science, 2016)

Uses of Innovative Modeling Tools within the Implementation of the Marine Strategy Framework Directive - Christopher P. Lynam; Laura Uusitalo; Joana Patrício; Chiara Piroddi; Ana M. Queirós; Heliana Teixeira; Axel G. Rossberg; Yolanda Sagarminaga; Kieran Hyder; Nathalie Niquil; Christian Möllmann; Christian Wilson; et al. (Frontiers in Marine Science, 2016)

Decrease in water clarity of the southern and central North Sea during the 20th century - Elisa Capuzzo; David Stephens; Tiago Silva; Jon Barry; Rodney M. Forster (Global Change Biology, 2015)
Light in the marine environment is a key environmental variable coupling physics to marine biogeochemistry and ecology. Weak light penetration reduces light available for photosynthesis, changing energy fluxes through the marine food web. Based on published and unpublished data, this study shows that the central and southern North Sea has become significantly less clear over the second half of the 20th century. In particular, in the different regions and seasons investigated, the average Secchi depth pre‐1950 decreased between 25% and 75% compared to the average Secchi depth post‐1950. Consequently, in summer pre‐1950, most (74%) of the sea floor in the permanently mixed area off East Anglia was within the photic zone. For the last 25+ years, changes in water clarity were more likely driven by an increase in the concentration of suspended sediments, rather than phytoplankton. We suggest that a combination of causes have contributed to this increase in suspended sediments such as changes in sea‐bed communities and in weather patterns, decreased sink of sediments in estuaries, and increased coastal erosion. A predicted future increase in storminess (Beniston et al ., 2007; Kovats et al ., 2014) could enhance the concentration of suspended sediments in the water column and consequently lead to a further decrease in clarity, with potential impacts on phytoplankton production, CO 2 fluxes, and fishery production.

A biofilm model developed to investigate survival and disinfection of Mycobacterium mucogenicum in potable water - Catherine R. Armbruster; Terri S. Forster; Rodney M. Donlan; Heather A. O'Connell; Alicia M. Shams; Margaret M. Williams (Biofouling, 2012)

Seasonal and interannual variation of the phytoplankton and copepod dynamics in Liverpool Bay - Naomi Greenwood; Rodney M. Forster; Veronique Créach; Suzanne J. Painting; Anna Dennis; Stewart J. Cutchey; Tiago Silva; David B. Sivyer; Tim Jickells (Ocean Dynamics, 2012)

Relationship of intertidal surface sediment chlorophyll concentration to hyperspectral reflectance and chlorophyll fluorescence - Jacco C. Kromkamp; Edward P. Morris; Rodney M. Forster; Claire Honeywill; Scott Hagerthey; David M. Paterson (Estuaries and Coasts, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)